Evaluation of waste materials for pollutant removal - Lai, Amy Hui Ting (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study was conducted to assess the capability of three waste materials in removing pollutants from synthetic and real wastewater samples. Column experiments with single (egg shells, shrimp shells and coal) and mixed medium (egg shells and coal; shrimp shells and coal) were carried out at room temperature. The removal efficiencies of TSS, PO4 3-, NH3-N, NO3-N, COD and heavy metals (Cd, Zn and Pb) were determined. All the waste materials showed good capability in removing heavy metals (Cd, Zn and Pb) from synthetic and real wastewater with removal efficiencies ranged between 90-100%. Of all the waste materials studied, egg shells showed the best adsorption and removal capability and this was supported by Langmuir adsorption studies using synthetic wastewater which revealed that egg shells had better capability in removing Cd (II) and Pb (II) ions compared to other waste materials. The influence of particle sizes for all single medium except shrimp shells was pursued and results showed that the smaller the particle size, the better is the removal capability of the waste materials except for the removal of COD using eggs shells. Egg shells with particle size 2 mm (18.67%) showed higher COD removal compared to 1 mm particle size (14.67%). However, statistical analysis showed that there was no significant difference in the removal by the two particle sizes. Waste materials also reduced the concentrations of TSS, PO4 3-, NH3-N, NO3-N, COD and heavy metals in real wastewater. Results of this study showed the effectiveness and feasibility of the proposed waste materials as treatment medium for wastewater.